1980
DOI: 10.1021/np50008a004
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Agents From Higher Plants. Antimicrobial Isoflavanoids and Related Substances From Glycyrrhiza glabra L. var. typica

Abstract: Bioassay-directed fractionation of Glycyrrhiza glabra L. var. typica resulted in the isolation and characterization of glabridin (I), glabrol (2), glabrene (3), 3-hydroxyglabrol (4), 4'-O-methylglabridin (5), 3'-methoxyglabridin (6), formononetin (7), phaseollinisoflavan (8), hispaglabridin A (9), hispaglabridin B (13), salicylic acid and O-acetyl salicylic acid. Of these, hispaglabridin A, hispaglabridin B, 4'-O-methylglabridin, glabridin, glabrol and 3-hydroxyglabrol possess significant antimicrobial activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 25 publications
2
70
0
7
Order By: Relevance
“…However, other parts of the plants such as latex, rhizome and resin etc., are also used in some of herbal preparation. The use of specific plant parts for specific disease treatment suggests that these parts have strongest certain active phyto-constituents against digestive complaints with no or less side effects (Mitscher et al, 1980). Moreover, the maximum use of leaves for remedy preparation might be due to the reason that it is main site of most of the physiological process that result in production of variety of active compounds as well as the collection of leaves poses no significant threat to the survival of individual plants (Poffenberger et al, 1992).…”
Section: General Overviewmentioning
confidence: 99%
“…However, other parts of the plants such as latex, rhizome and resin etc., are also used in some of herbal preparation. The use of specific plant parts for specific disease treatment suggests that these parts have strongest certain active phyto-constituents against digestive complaints with no or less side effects (Mitscher et al, 1980). Moreover, the maximum use of leaves for remedy preparation might be due to the reason that it is main site of most of the physiological process that result in production of variety of active compounds as well as the collection of leaves poses no significant threat to the survival of individual plants (Poffenberger et al, 1992).…”
Section: General Overviewmentioning
confidence: 99%
“…In addition, 29 known phenolic compounds were obtained and identified by comparison of physical and spectral data with those reported in the literature. The following known phenolic compounds were identified in the CHCl 3 -MeOH (19:1) fraction: echinatin (11, 5.4 mg) [5], lichocalcone B (12, 17.3 mg) [6], morachalcone A (13, 14.1 mg) [7], 2′,3,4′-trihydroxy-3′-γ,γ-dimethylallyl-6′′,6′′-dimethylpyrano[2′′,3′′:4,5]chalcone (14, 17.4 mg) [8], 1-(2′,4′-dihydroxyphenyl)-2-hydroxy-3-(4′′-hydroxyphenyl)-1-propanone (15, 5.8 mg) [9], kanzonol Y (16, 2.5 mg) [10], (3R)-vestitol (17, 10.5 mg) [11], (3R)-2′,3′,7-trihydroxy-4′-methoxyisoflavan (18, 8.1 mg) [12], kanzonol X (19, 37.1 mg) [10], glabridin (20,193 hispaglabridin A (23, 13.7 mg) [14], hispaglabridin B (24, 10.7 mg) [14], glabrene (25, 28.8 mg) [16], kanzonol W (26, 3.0 mg) [10], glabrocoumarin (27,16.4 mg) [17], shinpterocarpin (28,41.0 mg) [18], O-methylshinpterocarpin (29, 32.4 mg) [18], licoagrocarpin (30, 6.1 mg) [19], licoflavanone A (31, 4.8 mg) [20], glabrol (32, 13.5 mg) [13], shinflavanone (33, 7.8 mg) [18], euchrenone a5 (34, 1.5 mg) [21], xambioona (35,8.0 mg) [22], gancaonin L (36, 8.8 mg) [23], glabrone (37, 15.5 mg) [24], kanzonol U (38, 21.6 mg) [11], and 8,8-dimethyl-3,4-dihydro-2H,8H-pyrano[2,3-f]-chromon-3-ol (39, 17.4 mg) [25] (Figure 4). The structures of isolated compounds were classified into 12 groups: chalcones (1-4, 11-16), isoflavans (5, 6, 17-24), an isoflavone (25), 3-arylcoumarins (26, 27), pterocarpans (28-30), a flavone (31), a flava...…”
Section: Isolation and Structural Determination Of Phenolic Compoundsmentioning
confidence: 99%
“…The main constituent, glycyrrhizin, and the associated aglycone, glycyrrhetinic acid, are also used in modern medicine, whereas the phenolic constituents have been implicated in promoting improved health, particularly with regard to stomach ulcers [2]. Therefore, several research groups have investigated the phenolic constituents of licorice [3] and found that it has beneicial efects for health, including antimicrobial properties [4,5]. In this chapter, we summarize our studies on phenolic constituents and some of their pharmacological efects, including those linked to drug-resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%